Leibniz on Binary: The Invention of Computer Arithmetic by Lloyd Strickland and Harry Lewis (review). - Mckee, Samuel (Technology & Culture, 2025)
"Leibniz on Binary: The Invention of Computer Arithmetic" by Lloyd Strickland and Harry Lewis is a comprehensive collection of Gottfried Wilhelm Leibniz's writings on the binary system of computation. The authors provide historical context and examine Leibniz's contributions to binary arithmetic, asserting his role in bringing it to the modern world. The book delves into Leibniz's religious motivations and his quest for a mathematical understanding of the divine, making it valuable for scholars of technology, mathematics, computer science, and those interested in the theological origins of Leibniz's work.